PEMBANGUNAN SISTEM ABSENSI DAN GAJI BERBASIS WEBSITE MENGGUNAKAN AGILE FRAMEWORK STUDI KASUS AKADEMI TEKNOLOGI BANDUNG - Nadia Apriliani Hamidah (E-JOINT (Electronica and Electrical Journal Of Innovation Technology), 2023)
In the era of continually advancing information technology, information systems have become a crucial element in the management of institutions, including higher education institutions such as the Bandung Institute of Technology (Akademi Teknologi Bandung). Attendance and employee payroll management are vital aspects of the institution's operations. In this context, the implementation of a web-based attendance and payroll system becomes a relevant solution. As a leading educational institution, the Bandung Institute of Technology needs to modernize its technological infrastructure to optimize attendance and payroll management. A case study on the development of a web-based attendance and payroll system at the Bandung Institute of Technology aims to explore the potential improvements and efficiencies that can be gained through the application of information technology in attendance and payroll management. The objective is to ensure more accurate attendance recording, timely salary payments, and transparency in salary calculations for employees. Additionally, this system is expected to reduce the risk of human errors in administrative processes, ultimately enhancing productivity and service quality within the institution. The research method employed is the Agile Framework, which is increasingly utilized because it helps developers create software according to consumer needs. The design used in building this system utilizes PHP as the programming language, MySQL as the database, and Visual Studio Code as the editor. The system has been tested using various methods such as Black Box Testing and User Acceptance Testing to verify that all features and functions are functioning correctly. User Acceptance Testing results in a highly satisfactory status, with scores ranging from 92% to 96% across 11 assessment criteria.